Clinical Observation of Phacoemulsification Combined with Intravitreal Injection of Conbercept in Cataract Patients with Diabetic Macular Edema - Jing Wang; Yuqi Liu; Yiping Hu; Lu Lu; Kaili Tang; Jinsong Zhang (Journal of Ophthalmology)
Aim. To observe the clinical efficacy and safety of phacoemulsification surgery combined with intravitreal injection of conbercept in cataract patients with DME. Methods. This is a prospective clinical cohort study. Thirty-five cataract patients (49 eyes) with DME were divided into two groups. The observation group (23 eyes) underwent a cataract phacoemulsification surgery combined with intravitreal injection of conbercept 0.5 mg; the control group (26 eyes) underwent a cataract phacoemulsification surgery only. The visual acuity, central macular thickness (CMT), IOP, and anterior chamber flare were examined before surgery and 1 week and one month after surgery. Results. The UCVA and BCVA in Log MAR in the observation group were lower than those in the control group at 1 week (p=0.032; p=0.041) and 1 month (p=0.035; p=0.039), respectively, after the surgery. The CMT of the observation group changed from 492.7 ± 32.2 μm before surgery to 341.6 ± 59.9 μm one week after surgery and 374.8 ± 48.3 μm one month after surgery. The CMT of control group increased after surgery. There was no significant difference in IOP and flare between the two groups at all following times. Conclusion. In patients with DME, undergoing a cataract surgery combined with intravitreal injection of conbercept is safe and effective for visual improvement and CMT declination with relatively fewer IOP and flare fluctuation.